Preparation method of nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material, obtained product and application

By using nitrogen-doped three-dimensional porous carbon-loaded petal-like molybdenum disulfide composite in electrochemical sensors, the problem of difficulty in simultaneously conducting dopamine and uric acid detection in the prior art is solved, and a wider detection range is achieved. Higher selectivity.

CN119492792APending Publication Date: 2025-02-21QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411774121.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art is difficult to detect and distinguish dopamine and uric acid simultaneously, and the detection range is narrow, and the structure-effect relationship between electrochemical catalyst structure and catalytic performance is not fully explored.

Method used

Using nitrogen-doped three-dimensional porous carbon-loaded petal-like molybdenum disulfide composite material, the MoS2 nanoflowers are anchored on a multi-stage porous three-dimensional nitrogen-doped porous carbon support, forming a strong metal-carrier interaction, promoting charge transfer and improving electricity Catalytic properties.

Benefits of technology

High sensitivity and selective detection of dopamine and uric acid are achieved, and the detection range is expanded to 0.01-989.95 µM and 0.6-1063.4 µM, significantly improving electrocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119492792A_ABST
    Figure CN119492792A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical sensor functional materials. The invention particularly relates to a preparation method of a nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material, an obtained product and application. The nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material provided by the invention is a porous material and comprises the elements of C, N, S and Mo. The nitrogen-doped three-dimensional porous carbon has a multilevel porous three-dimensional network structure, Mo and S elements are loaded on the surface and inside the nitrogen-doped three-dimensional porous carbon, and the nitrogen-doped three-dimensional porous carbon mainly exists in the form of a MoS2 compound and is of a petal-shaped structure. Wherein strong metal-carrier interaction exists between the nitrogen-doped three-dimensional porous carbon and the MoS2. The nitrogen-doped three-dimensional porous carbon provided by the invention has a large specific surface area and excellent conductivity, so that the conductivity of the prepared composite material is improved, and the stacking problem of MoS2 is avoided. The generation of the petal-shaped MoS2 nanosheets is beneficial to shortening of a transfer route and promotion of rapid transmission and diffusion of electron ions. The strong metal-carrier interaction between the nitrogen-doped three-dimensional porous carbon and MoS2 can provide charge transfer, enhance the electro-catalytic performance, and facilitate electro-catalysis and distinguishing of electroactive biological micromolecules dopamine and uric acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical sensor functional materials, and specifically relates to a preparation method of a nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material, and the obtained product and application. Background Art

[0002] Electroactive biomolecules dopamine and uric acid play a vital role in human metabolism, and abnormal levels of them often lead to the occurrence of many diseases and have a significant impact on human health. It is worth noting that dopamine and uric acid often coexist in biological matrices. Currently, various techniques have been used to detect dopamine and uric acid, including high-performance liquid chromatography-mass spectrometry, fluorescence, colorimetry, and electrochemical sensing. In particular, electrochemical sensors that integrate functional nanomaterials with low cost, simple operation, good selectivity, adjustable structure, and sensitive electrochemical response have performed well in the detection of biomolecules, especially electroactive biomolecules. It is well known that the electrode material may directly determine the performance of the sensor. First, it can provide a large surface area as a substrate to increase the electrolyte contact area. In addition, it can also serve as an electrocatalytic active site for electroactive substances to enhance the signal. Therefore, designing electrode materials with excellent catalytic activity is crucial to improve the performance of electrochemical sensors. However, previously reported sensing materials, such as graphene, noble metal nanomaterials, and polymer nanomaterials, although effective, still suffer from problems such as high fabrication cost, low sensitivity, narrow detection range, and poor catalytic activity.

[0003] In recent years, transition metal sulfides have attracted great attention in the field of electrochemistry due to their unique electronic structure and excellent electrochemical activity. Molybdenum disulfide is structurally similar to graphite and has a d-band electronic structure similar to that of Pt group metals. In addition, MoS2 has good biocompatibility, excellent stability, tunable structure, and unique energy enhancement behavior. Therefore, MoS2 has great prospects in biosensing. However, the poor electrochemical conductivity of MoS2 hinders charge transfer, and MoS2 nanosheets are easily stacked due to van der Waals interactions, which reduces the number of active sites and limits their practical applications. The literature "Simultaneous electrochemical determination of dopamine and uric acid based on MoS 2nanoflowers-graphene / ITOelectrode" reported that indium tin oxide glass modified with molybdenum disulfide nanoflowers-graphene was used for electrochemical detection of dopamine and uric acid. The reported detection range was 0-60 µM for both dopamine and uric acid. However, the following problems still need to be solved in the disclosed inventions for dopamine and uric acid detection: 1) it is impossible to simultaneously detect and distinguish dopamine and uric acid; 2) the detection range is narrow; 3) the structure-activity relationship between the electrochemical catalyst structure and catalytic performance needs to be further explored. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing a nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material.

[0005] The present invention also provides a nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material obtained by the above-mentioned preparation method. The composite material has a strong metal-carrier interaction and is an electrochemical sensing porous material with high sensitivity and high selectivity for dopamine and uric acid in the range of 0.01-989.95 µM and 0.6-1063.4 µM, respectively; and the three-dimensional nitrogen-doped porous carbon network with a unique porous structure and the petal-shaped MoS 2 Starting from the electronic structure modification with strong metal-support interaction, MoS 2 The nanoflowers are anchored on a hierarchical porous three-dimensional nitrogen-doped porous carbon support to form a nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material to induce a strong metal-support interaction effect, promote charge transfer, and help improve the electrocatalytic performance.

[0006] Another object of the present invention is to provide an application of the above-mentioned nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material in the detection and differentiation of electroactive biological small molecules dopamine and uric acid.

[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: The present invention provides a method for preparing a nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material, comprising the following steps: (1) Dissolve sodium chloride, sodium carbonate and ammonium citrate in deionized water and stir to obtain a clear solution A; (2) freeze-drying solution A to obtain a solid product; grinding the solid product and calcining it at high temperature to obtain a black powder; washing the black powder and vacuum drying it to obtain nitrogen-doped three-dimensional porous carbon; (3) Ammonium molybdate tetrahydrate, thiourea and nitrogen-doped three-dimensional porous carbon are dispersed in deionized water, stirred and subjected to a hydrothermal reaction to obtain a nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material.

[0008] Furthermore, in step (1), the mass ratio of the sodium chloride, sodium carbonate and ammonium citrate is 4:0.1:0.3; and the concentration of the sodium chloride in deionized water is 0.2-0.3 g / mL.

[0009] Furthermore, in step (1), the stirring is performed at room temperature for 8 hours.

[0010] Furthermore, in step (2), the freeze drying is to quickly freeze solution A in liquid nitrogen and then dry it; the freeze drying is to first quickly freeze solution A in liquid nitrogen and then freeze dry it at a temperature of -60°C for 24 h.

[0011] Furthermore, in step (2), the high temperature calcination is carried out by increasing the temperature to 700°C at a heating rate of 5°C / min and keeping the temperature for 30 min; the high temperature calcination is carried out in an inert gas atmosphere; and the inert gas is argon.

[0012] Furthermore, in step (3), the molar ratio of the ammonium molybdate tetrahydrate to thiourea is 0.05 mmol:1.4 mmol; and the mass ratio of the ammonium molybdate tetrahydrate to the nitrogen-doped three-dimensional porous carbon is 3:1.

[0013] Furthermore, in step (3), the temperature of the hydrothermal reaction is 200° C. and the reaction time is 24 h.

[0014] The present invention also provides a nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material prepared by the above preparation method.

[0015] The present invention also provides the application of the above nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material in the field of electroactive bio-small molecule electrochemical sensors.

[0016] Furthermore, the application of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material in the detection and identification of electroactive biological small molecules dopamine and uric acid, and anti-interference detection in the field of electrocatalytic sensing specifically includes the following steps: (1) Electrode pretreatment: polish the glassy carbon electrode in an alumina suspension, rinse with water and ethanol, ultrasonicate, and place for later use; (2) preparing ink: mixing the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material, ethanol, deionized water and naphthol, ultrasonicating and dispersing to form solution B; (3) Construction of electrocatalytic sensing interface: Take solution B and quickly drop it on the pretreated electrode surface and leave it to form a uniform sensing interface.

[0017] Furthermore, in step (1), the diameter of the glassy carbon electrode used is 3 mm, and the particle size of the aluminum oxide is 0.5 µm and 0.03 µm.

[0018] Furthermore, in step (2), the ratio of nitrogen-doped three-dimensional porous carbon-supported petal-shaped MoS2 composite material, ethanol, deionized water and naphthol (5 wt.%) was 1 mg: 100 µL: 50 µL: 20 µL.

[0019] Furthermore, in step (3), the volume of solution B required for the electrocatalytic sensing interface is 7 µL.

[0020] The nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material provided by the present invention is a porous material, and the element composition includes C, N, S, and Mo elements. The nitrogen-doped three-dimensional porous carbon has a multi-level porous three-dimensional network structure, and the surface and interior of the nitrogen-doped three-dimensional porous carbon are loaded with Mo and S elements, mainly MoS 2 The compound exists in the form of a petal-like structure. The nitrogen-doped three-dimensional porous carbon and MoS 2 There is a strong metal-support interaction between them.

[0021] Nitrogen-doped three-dimensional porous carbon has a large specific surface area and excellent electrical conductivity, which is beneficial to improve the electrical conductivity of the prepared composite material and avoid MoS 2 The stacking problem of petal-shaped MoS 2 The generation of nanosheets is beneficial to shorten the transfer route and promote the rapid transmission and diffusion of electrons and ions. 2 The strong metal-support interaction can provide charge transfer and enhance the electrocatalytic performance, which is beneficial to the electrocatalysis and differentiation of electroactive biological small molecules dopamine and uric acid.

[0022] The beneficial effects of the present invention are: (1) Simple preparation method: Compared with the prior art, the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material designed by the present invention has a simple operation method, controllable morphology, environmental protection and low cost. The synthesis process only involves one high-temperature calcination and synthesis to obtain the desired product; (2) Novel design of structure and performance: The present invention synthesizes a petal-shaped molybdenum disulfide composite material with nitrogen-doped three-dimensional porous carbon by one-step calcination and hydrothermal treatment. 2The strong metal-carrier interaction between them can provide charge transfer and enhance electrocatalytic performance, which is beneficial to the electrocatalysis and differentiation of electroactive biological small molecules dopamine and uric acid. The prepared electrochemical biosensor can detect and differentiate dopamine and uric acid in phosphate buffer solution (0.2 M, pH 7.4), with a wide linear detection range (dopamine: 0.01-989.95 µM, uric acid: 0.6-1063.4µM) and high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 1 is a SEM image of a prepared nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material; wherein Figure a is a SEM image of nitrogen-doped three-dimensional porous carbon, and Figure b is a SEM image of nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material; Figure 2 1 is an XPS graph of the prepared nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material; wherein FIG. a is a Mo 3d graph of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material and molybdenum disulfide, and FIG. b is a S 2p graph of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material and molybdenum disulfide; Figure 3 This is the SEM image of molybdenum disulfide prepared in Comparative Example 1; Figure 4 The electrochemical sensor constructed based on the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material prepared in Example 1 simultaneously catalyzes and distinguishes dopamine and uric acid; Figure 5 This is a linear curve of dopamine catalysis by an electrochemical sensor constructed based on the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material prepared in Example 1; Figure 6 This is a linear curve of uric acid catalysis by an electrochemical sensor constructed based on the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material prepared in Example 1; Figure 7 The electrochemical sensor constructed based on the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material prepared in Example 1 catalyzes the selective test of dopamine and uric acid; Figure 8 The linear curve of dopamine catalysis by the electrochemical sensor constructed based on molybdenum disulfide prepared in Comparative Example 1; Fig. 9 This is the linear curve of the electrochemical sensor constructed based on molybdenum disulfide prepared in Comparative Example 1 for catalyzing uric acid. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further explained and illustrated by means of specific embodiments below.

[0025] Example 1 (1) First, 20 g of sodium chloride, 0.5 g of sodium carbonate, and 1.5 g of ammonium citrate were dissolved in 70 mL of deionized water and stirred at room temperature for 8 h to obtain a clear solution; then the solution was quickly frozen in liquid nitrogen and freeze-dried in a freeze dryer at -60 °C for 24 h to obtain a white solid. The solid was ground and annealed in a tube furnace at 700 °C in an Ar atmosphere for 30 min to obtain a black powder. The black powder was then washed several times with deionized water to remove the salt template and vacuum dried at 60 °C for 12 h to produce the final nitrogen-doped three-dimensional porous carbon N-3DPC.

[0026] (2) 0.05 mmol of ammonium molybdate tetrahydrate, 1.4 mmol of thiourea and a certain amount of N-3DPC (the mass ratio of ammonium molybdate tetrahydrate to nitrogen-doped three-dimensional porous carbon is 3:1) were dispersed in 20 mL of deionized water, stirred for 30 min, and then placed in a Teflon stainless steel hydrothermal reactor at 200°C for hydrothermal reaction for 24 h. Finally, the reaction solution was filtered and dried in a vacuum at 40°C for 10 h to obtain a nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material.

[0027] Figure 1 Figure a is a SEM image of the nitrogen-doped three-dimensional porous carbon prepared in Example 1, showing a 3D interpenetrating ultra-thin nitrogen-doped carbon network with a multi-level porous structure. Figure 1 Figure b is a SEM image of the nitrogen-doped three-dimensional porous carbon-loaded petal-shaped MoS2 composite material. It can be clearly seen that MoS2 is successfully grown on the surface of the nitrogen-doped three-dimensional porous carbon skeleton and in the internal closed pores. 2 The nanosheets aggregated to form rose-like nanoflowers without stacking, and the nitrogen-doped three-dimensional porous carbon framework was not destroyed.

[0028] Figure 2 : This is an XPS graph of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped MoS2 composite material prepared in Example 1; wherein Figure a is a Mo 3d graph of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped MoS2 composite material and MoS2, and Figure b is a S 2p graph of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped MoS2 composite material and MoS2. The high-resolution Mo 3d spectrum of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped MoS2 composite material depicts two characteristic peaks at 229.0 eV and 232.0 eV, corresponding to 1T MoS 2 Mo 3d 5 / 2 and Mo 3d 3 / 2 At the same time, Mo 3d 5 / 2 (230.1 eV) and Mo3d 3 / 2(233.2 eV) Two signals related to 2H MoS 2 Related, indicating that Mo 4+ In addition, two relatively weak Mo 3d 3 / 2 (VI) peak, which may belong to Mo oxide 6+ At the same time, a weak peak appears at 226.3 eV, corresponding to S 2s, and S 2p XPS spectra provide good evidence for the existence of two peaks at 162.0 eV and 163.2 eV, respectively, attributed to S 2- 2p 3 / 2 and S 2- 2p 1 / 2 . It is attractive that, compared with pure MoS 2 In comparison, the binding energies of Mo 3d and S 2p in the petal-shaped MoS2 composite supported by nitrogen-doped 3D porous carbon show a slight negative shift, indicating that the valence electrons of Mo and S increase, further supporting the MoS 2 Electron transfer occurred between the N-3DPC supports, leading to strong metal-support interactions, which could have a significant impact on improving the performance of the sensor.

[0029] Comparative Example 1 0.05 mmol of ammonium molybdate tetrahydrate and 1.4 mmol of thiourea were dispersed in 20 mL of deionized water, stirred for 30 min, and then placed in a Teflon stainless steel hydrothermal reactor at 200 °C for 24 h. Finally, the reaction solution was filtered and dried in a vacuum at 40 °C for 10 h to obtain nano-spherical molybdenum disulfide.

[0030] Depend on Figure 3 As shown, MoS2 aggregates into flower-like spheres, in which the individual nanospheres are large and heavily stacked.

[0031] Effect Example 1 (1) Electrode pretreatment: A glassy carbon electrode with a diameter of 3 mm was polished in 0.5 and 0.03 µm alumina suspensions, rinsed with water and ethanol, ultrasonicated, and placed aside for later use.

[0032] (2) The nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material prepared in Example 1 was mixed with ethanol, deionized water and naphthol in a ratio of 1 mg: 100 μL: 50 μL: 20 μL to prepare an ink, and ultrasonically dispersed into a uniform solution.

[0033] (3) Take 7 µL of the above solution and drop it on the surface of the pretreated electrode to form a uniform sensing interface.

[0034] Figure 4 The electrochemical sensor constructed based on nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material simultaneously catalyzes and distinguishes dopamine and uric acid. In a phosphate buffer solution (0.2 M, pH 7.4) containing 200 µM dopamine and 500 µM uric acid, the catalytic ability of the sensor to dopamine and uric acid was tested using differential pulse voltammetry (electrochemical workstation, CH760E, Shanghai Chenhua). It can be clearly found that the sensor has a significant current response to both dopamine and uric acid, and the peak currents of the two can be clearly distinguished. This shows that in the presence of uric acid and dopamine at the same time, the constructed electrochemical sensor can effectively distinguish the signals of uric acid and dopamine. The differential pulse voltammetric response of the electrochemical sensor constructed based on molybdenum disulfide prepared in Comparative Example 1 to dopamine and uric acid. The catalytic ability of the sensor to dopamine and uric acid was tested by differential pulse voltammetry in a phosphate buffer solution (0.2 M, pH 7.4) containing 200 µM dopamine and 500 µM uric acid. It can be clearly found that the differential pulse voltammetry peaks of dopamine and uric acid overlap, indicating that the sensor cannot detect and distinguish between dopamine and uric acid.

[0035] Figure 5 The linear curve of dopamine catalysis by an electrochemical sensor based on nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material. In phosphate buffer solution, the it test technique was used to test a series of dopamine concentration gradients at a voltage of 0.35 V using a 10 µL syringe with a constant magnetic stirring interval of 50 s. The linear range of the constructed sensor for dopamine detection is 0.01 ~ 989.95 µM, and the minimum detection limit is as low as 3 nm, which shows a wider linear range and lower detection limit than the existing technology.

[0036] Figure 6 The linear curve of uric acid catalysis by an electrochemical sensor based on nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material. In phosphate buffer solution, the it test technique was used to test the continuous addition of a series of uric acid concentration gradients at a voltage of 0.40 V using a 10 µL syringe under constant magnetic stirring at intervals of 50 s. The constructed sensor has a linear range of 0.6-1063.4 µM µM for uric acid detection, and the minimum detection limit is as low as 200 nm, which shows a wider linear range and lower detection limit than the existing technology, and is 1 to 3 orders of magnitude better than the existing technology.

[0037] Figure 7The electrochemical sensor constructed based on nitrogen-doped three-dimensional porous carbon supported petal-shaped molybdenum disulfide composite material was used to selectively test dopamine and uric acid. The electrochemical sensors were constructed based on nitrogen-doped three-dimensional porous carbon supported petal-shaped molybdenum disulfide composite material ... + , 0.5 mM Cl - , 0.5 mM Na + The selectivity of the sensor to dopamine and uric acid was tested by differential pulse voltammetry in a phosphate buffer solution (0.2 M, pH 7.4) containing 1.0 mM carbonate. The results showed that the constructed sensor only showed current response to dopamine and uric acid, reflecting the excellent selectivity of the constructed sensor to dopamine and uric acid.

[0038] Figure 8 The linear curve of dopamine catalysis by the electrochemical sensor constructed based on molybdenum disulfide prepared in Comparative Example 1. In a phosphate buffer solution, the it test technique was used to test the continuous addition of a series of dopamine concentration gradients at a voltage of 0.40 V using a 10 µL syringe with a constant magnetic stirring interval of 50 s. The linear range of the constructed sensor for dopamine detection is 1.5 ~ 524 µM, and the minimum detection limit is 500 nm, which is much worse than the electrochemical sensor constructed by the nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material prepared in Example 1.

[0039] Fig. 9 The linear curve of uric acid catalysis by the electrochemical sensor constructed based on molybdenum disulfide prepared in Comparative Example 1. In phosphate buffer solution, the it test technique was used to test the continuous addition of a series of uric acid concentration gradients at a voltage of 0.50V using a 10 µL syringe under constant magnetic stirring for 50 s. The linear range of the constructed sensor for uric acid detection is 1-420 µM µM, and the minimum detection limit is as low as 333 nm, which is much worse than the electrochemical sensor constructed by nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material.

Claims

1. A method for preparing a nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material, characterized in that: The following steps are involved: (1) Dissolve sodium chloride, sodium carbonate and ammonium citrate in deionized water and stir to obtain a clear solution A; (2) freeze-drying solution A to obtain a solid product; The solid product is ground and then calcined at high temperature to obtain a black powder; The black powder was washed and vacuum dried to obtain nitrogen-doped three-dimensional porous carbon; (3) Ammonium molybdate tetrahydrate, thiourea and nitrogen-doped three-dimensional porous carbon are dispersed in deionized water, stirred and subjected to a hydrothermal reaction to obtain a nitrogen-doped three-dimensional porous carbon-loaded petal-shaped molybdenum disulfide composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the sodium chloride, sodium carbonate and ammonium citrate is 4:0.1:0.3; and the concentration of the sodium chloride in deionized water is 0.2-0.3 g / mL.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the stirring is performed at room temperature for 8 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step (2), the freeze drying is to quickly freeze solution A in liquid nitrogen and dry it; the freeze drying is to first quickly freeze solution A in liquid nitrogen and then freeze dry it at a temperature of -60°C for 24 h.

5. The preparation method according to claim 1 or 4, characterized in that: In step (2), the high temperature calcination is carried out by increasing the temperature to 700°C at a heating rate of 5°C / min and keeping the temperature for 30 min; the high temperature calcination is carried out in an inert gas atmosphere; the inert gas is argon.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (3), the molar ratio of the ammonium molybdate tetrahydrate to thiourea is 0.05 mmol:1.4 mmol; and the mass ratio of the ammonium molybdate tetrahydrate to the nitrogen-doped three-dimensional porous carbon is 3:

1.

7. The preparation method according to claim 1 or 6, characterized in that: In step (3), the temperature of the hydrothermal reaction is 200°C and the reaction time is 24 h.

8. A nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material as claimed in claim 8 in the field of electroactive bio-small molecule electrochemical sensors.

10. The use according to claim 9, characterized in that: The application of the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material in the detection and identification of electroactive biological small molecules dopamine and uric acid, and anti-interference detection in the field of electrocatalytic sensing specifically comprises the following steps: (1) Electrode pretreatment: polish the glassy carbon electrode in an alumina suspension, rinse with water and ethanol, ultrasonicate, and place for later use; (2) preparing ink: mixing the nitrogen-doped three-dimensional porous carbon-supported petal-shaped molybdenum disulfide composite material, ethanol, deionized water and naphthol, ultrasonicating and dispersing to form solution B; (3) Construction of electrocatalytic sensing interface: Take solution B and quickly drop it on the pretreated electrode surface and leave it to form a uniform sensing interface.